Real‐Time and High‐Resolution Bioimaging with Bright Aggregation‐Induced Emission Dots in Short‐Wave Infrared Region. Issue 12 (17th January 2018) - Qi, Ji; Sun, Chaowei; Zebibula, Abudureheman; Zhang, Hequn; Kwok, Ryan T. K.; Zhao, Xinyuan; Xi, Wang; Lam, Jacky W. Y.; Qian, Jun; Tang, Ben Zhong
Abstract: Fluorescence imaging in the spectral region beyond the conventional near‐infrared biological window (700–900 nm) can theoretically afford high resolution and deep tissue penetration. Although some efforts have been devoted to developing a short‐wave infrared (SWIR; 900–1700 nm) imaging modality in the past decade, long‐wavelength biomedical imaging is still suboptimal owing to the unsatisfactory materials properties of SWIR fluorophores. Taking advantage of organic dots based on an aggregation‐induced emission luminogen (AIEgen), herein microscopic vasculature imaging of brain and tumor is reported in living mice in the SWIR spectral region. The long‐wavelength emission of AIE dots with certain brightness facilitates resolving brain capillaries with high spatial resolution (≈3 µm) and deep penetration (800 µm). Owning to the deep penetration depth and real‐time imaging capability, in vivo SWIR microscopic angiography exhibits superior resolution in monitoring blood–brain barrier damage in mouse brain, and visualizing enhanced permeability and retention effect in tumor sites. Furthermore, the AIE dots show good biocompatibility, and no noticeable abnormalities, inflammations or lesions are observed in the main organs of the mice. This work will inspire new insights on development of advanced SWIR techniques for biomedical imaging. Abstract : By employing bright near‐infrared (NIR) aggregation‐induced emission (AIE) dots and short‐wave infrared imaging systems, brain capillaries with high spatial resolution (≈3 µm) and deep penetration (800 µm) in living mice are resolved. Owing to the large penetration depth and real‐time imaging capability, the AIE dots enable superior resolution in probing blood–brain barrier damage in the mouse brain, and visualizing enhanced permeability and retention effect in tumor sites.